New antiproliferative agents derived from tricyclic 3, 4‐dihydrobenzo[4, 5]imidazo[1, 2‐a][1, 3, 5]triazine scaffold: Synthesis and pharmacological effects. Issue 11 (29th July 2022) - Robello, Marco; Salerno, Silvia; Barresi, Elisabetta; Orlandi, Paola; Vaglini, Francesca; Banchi, Marta; Simorini, Francesca; Baglini, Emma; Poggetti, Valeria; Taliani, Sabrina; Da Settimo, Federico; Bocci, Guido
Abstract: A series of novel 3, 4‐dihydrobenzo[4, 5]imidazo[1, 2‐ a ][1, 3, 5]triazine (BIT) derivatives were designed and synthesized. In vitro antiproliferative activity was detected toward two human colorectal adenocarcinoma cell lines (CaCo‐2 and HT‐29) and one human dermal microvascular endothelial cell line (HMVEC‐d). The most active compounds, namely 2‐4 and 8, were further investigated to clarify the mechanism behind their biological activity. Through immunofluorescence assay, we identified the target of these molecules to be the microtubule cytoskeleton with subsequent formation of dense microtubule accumulation, particularly at the periphery of the cancer cells, as observed in paclitaxel‐treated cells. Overall, these results highlight BIT derivatives as robust and feasible candidates deserving to be further developed in the search for novel potent antiproliferative microtubule‐targeting agents. Abstract : A series of novel 3, 4‐dihydrobenzo[4, 5]imidazo[1, 2‐ a ][1, 3, 5]triazine derivatives were designed, synthesized, and investigated for their in vitro antiproliferative activity on two human colorectal adenocarcinoma cell lines and one human dermal microvascular endothelial cell line. The target of the most active compounds (2‐4, 8 ) was identified as the microtubule cytoskeleton, with subsequent dense microtubule accumulation.